Insect Pests and Diseases in Stored Sorghum (Sorghum bicolor L.) and Maize (Zea mays L.) in West Hararghe, Ethiopia - Gelana Keno Beyene; Amin Mohammed Yones; Ahmed Beyan Heji; Mukaddes Kayim (Advances in Agriculture)
The presence of major insect pests and microflora in stored sorghum and maize in West Hararghe, Ethiopia, poses a significant threat to food security and agricultural productivity, leading to postharvest losses and economic hardship for local farmers. This study aimed to evaluate and identify the main grain insect pests and diseases of stored maize and sorghum in West Hararghe, Ethiopia. The survey was carried out in five major sorghum and maize-producing districts of the surveyed areas, namely, Mieso, Gemechis, Tullo, Anchar, and Oda Bultum. The results revealed that maize and sorghum grains stored in sacks, ground pits, markets, and hanging (maize cob) storage containers were infested with insect species: maize weevil (S. zeamais), Angoumois grain moth (S. cerealella), rice weevil (S. oryzae), Red flour beetle (T. castaneum), confused flour beetle (T. confusum), and Lesser grain borer (R. dominica). The mean levels of major insect pest infestations and associated percentages of grain damage, weight loss, and germination loss were recorded across all traditional storage systems, including sacking, marketing, hanging or maize cob, and ground pit storage methods. The highest absolute frequency and relative frequency of F. oxysporum (14.53%), followed by A. flavus (13.08%), on maize seeds were recorded in the agar plate test. A total of eight species of fungi, including Fusarium species, A. parasiticus, and A. niger, were identified using the blotter and agar plate method. The incidence of fungal diseases was markedly high (98.33%) in maize grain stored in the Anchar district, followed closely by grain stored in the market in the same district, recording 98.33%. Therefore, it is recommended that further confirmatory identification using molecular tools be conducted to develop novel management strategies for these insect pests and diseases.